TRAF2 regulates the progression of pulmonary fibrosis through β-catenin-Snail signaling pathway - Wan, Zhijie; Gu, Jingwen; Duan, Wanli; Chen, Yuanyuan; Song, Shuya; Luo, Jingyu; Zhang, Xide; Yang, Yanyong; Gao, Fu; Xu, Ying (Frontiers in Public Health, 2025)
IntroductionPulmonary fibrosis (PF) is a devastating lung disease characterized by excessive extracellular matrix deposition and impaired pulmonary function, with limited therapeutic options. The pathogenesis of PF involves a complex network of molecular events, including epithelial-mesenchymal transition (EMT), activation of fibroblasts, and dysregulated tissue remodeling. Recent studies have identified TRAF2 (TNF receptor-associated factor 2) as a potential modulator of fibrosis, while its precise mechanism remains unclear.MethodsWe assessed TRAF2 expression and subcellular localization via immunofluorescence and Western blot. TRAF2 knockdown was achieved through siRNA transfection. Protein and mRNA levels of molecules were detected using wb and RT-qPCR. Molecular interactions (TRAF2/β-catenin/Snail) were validated by co-immunoprecipitation assays. HE staining and Masson staining were quantified.ResultsWe demonstrate that TRAF2 translocates to the nucleus after fibrosis induction and is positively correlated with disease severity. TRAF2 knockdown significantly reduced collagen deposition and myofibroblast activation, thereby alleviating fibrosis. Furthermore, we investigate the molecular mechanisms by which TRAF2 regulates pulmonary fibrosis, specifically its interaction with β-catenin and Snail, which promotes β-catenin-mediated transcriptional activation and facilitates EMT. These findings offer novel insights into the role of TRAF2 in pulmonary fibrosis, suggesting that TRAF2 may provide a promising therapeutic strategy for this debilitating disease.DiscussionOur study provides valuable insights into the role of TRAF2 in pulmonary fibrosis, while the precise molecular mechanisms by which TRAF2 interacts with β-catenin and Snail in fibrosis remain unclear. Future studies should aim to explore the mechanisms of TRAF2 in more detail, particularly how it interfaces with fibrotic mediators and cellular processes.